The Impact of Macroprudential Policies on the Vulnerability of the Banking System: Dynamic Panel Model - Nafiseh Keshtgar; Mosayeb Pahlavani; Seyed Hossein Mirjalili (Journal of Money and Economy, 2020)
In the aftermath of the global financial crisis (2007-2009), policymakers in the developing countries and emerging economies have generally relied on macroprudential policies to achieve financial stability. Since the banking system's vulnerability plays an essential role in financial instability, and the banking system's stability is exposed to vulnerability, we examine macroprudential policies' effectiveness in reducing banking vulnerability and economic instability through containing credit growth. We estimated a dynamic panel for 14 Iranian banks using GMM and Arellano Bovar / Blundell-bond two-stage estimators during 2009-2018. The results indicate that the increase in lending rates in the interbank market leads to the banking system's contraction of lending capacity. The positive and significant effect of the economic growth index indicates the banks' procyclical behavior. That financial institutions in the business cycles behave procyclical in lending. The diminishing effect of the macroprudential policy index on the bank credit expansion indicates that macroprudential authority and policy tools' application reduces the banking system's instability and vulnerability. Therefore, to reduce financial intermediation instability, the financial sector regulator can institutionalize macroprudential policies.
Keywords: C22; C82; E32; E44; G01; 330; Bank Credit; Macroprudential Policy; GMM Dynamic Panel; Iranian Banking